(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
School is a place where the transmission of diseases is easy, resulting from the interaction between students and instructors. In this study, we consider the application of the Homotopy Perturbation Method (HPM) to solve a mathematical model of disease dynamics in schools. The model equation consists of five classes: the susceptible class , the infected and careless class , the infected and unhygienic class , the infected and aware class , and the recovered class . The non-linear differential model equations are transformed into a series of linear differential equations, enabling faster derivation of approximate solutions.